The Influence of Discipline, Work Skills and Work Environment on Work Productivity - Erina Rulianti; Dita Herdidayanti (Kusuma Negara Business School, 2021)
Productivity in organizations is basically centered on human resources owned by an organization. Given that human resources are important, attention, direction and management of human resources must be carried out and applied within the organization in order to achieve an organizational productivity goal. Therefore, organizations need employees who are skilled at work and a good work environment in order to realize employee work productivity, besides that the discipline of individual employees is also very necessary to increase productivity whose achievements are also the goals of the company. The purpose of this study was to determine how much influence discipline, skills and work environment have on employee productivity. The research sample was 92 people and data were collected using a questionnaire questionnaire method, the data analysis technique used multiple linear regression test with the help of SPSS version 26 statistical program. The results of this study prove that discipline has a positive and insignificant effect on employee work productivity. Work skills have a positive and significant effect on employee work productivity. The work environment has a positive and significant effect on employee productivity. The conclusion of this study is that the discipline variable does not have a partial effect on work productivity, while the skills and work environment variables have a partial influence on work productivity.